The consequences of own and spousal disability on labor market outcomes and subjective well-being: evidence from Germany - Nils Braakmann (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2010)
In this paper, I contrast the effects of individual and spousal disability on subjective wellbeing and labor supply using data on couples from the German Socio-Economic Panel for the years 1984 to 2006. I find that both men and women reduce their propensity to work when they or their partner become disabled. The effects of spousal disability are economically large. I find no evidence for hours and wage adjustments by spousal disability, although there are wage effects of individual disability. The life-satisfaction of women, but not of men, is reduced considerably by their partners' disability. The effects are about 33 to 50% as large as those of individual disability. I also find no evidence that individuals adapt to their partners' disability, although there is adaption to individual disability.
Keywords: D64; I10; J14; 330; Disability; labor supply; subjective well-being; adaption; other-regarding preferences